Nitrogen-doped carbon nanofiber negative electrode material of lithium ion battery and preparation method of nitrogen-doped carbon nanofiber negative electrode material

By using carbon sources such as nitrogen heterocyclic rings and polycyclic aromatic hydrocarbons, combined with transition metal salts, a nitrogen-doped carbon nanofiber negative electrode material with bamboo-like hollow nitrogen-doped carbon nanotube graphite fiber shell and solid graphite fiber core layer was prepared. , solves the shortcomings of existing lithium-ion battery materials in high energy density and cycle stability, and realizes a high performance and low energy consumption preparation process.

CN119480974APending Publication Date: 2025-02-18XINYANG NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411591970.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

Smart Images

  • Figure CN119480974A_ABST
    Figure CN119480974A_ABST
Patent Text Reader

Abstract

The invention discloses a nitrogen-doped carbon nanofiber negative electrode material of a lithium ion battery and a preparation method of the nitrogen-doped carbon nanofiber negative electrode material. The nitrogen-doped carbon nanofiber negative electrode material has a tubular core-shell structure, a shell layer is a bamboo-like hollow nitrogen-doped carbon nanotube graphite fiber shell layer which grows longitudinally, and an inner core layer is a graphite fiber core layer which grows transversely in a V shape and is of a solid structure. Wherein the shell layer presents a graphene layer which is longitudinally arranged and grown and a hollow structure, so that the electronic conductivity of the carbon fiber is remarkably improved, and the structural toughness of the fiber is maintained; the inner core layer is a graphene layer arranged in a transverse V shape, open pores and expanded graphene gaps increase the number of lithium storage active sites, electrolyte ion diffusion is accelerated, and the effects of stabilizing the fiber structure and enhancing the mechanical strength are achieved. The nitrogen-doped carbon nanofiber material provided by the invention shows higher specific capacity, cycle performance and rate capability in lithium ion battery application, and is low in preparation cost, simple in method and easy to realize industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery negative electrode materials, and in particular to a lithium ion battery nitrogen-doped carbon nanofiber negative electrode material with a novel structure and a preparation method thereof. Background Art

[0002] At present, with the development demand of miniaturization, high energy and portability of electronic appliances, portable electronic products such as wearable devices have been rapidly developed. As its core component, flexible lithium-ion batteries have attracted close attention from researchers due to their high energy density, high operating voltage, fast charging speed, long cycle life, environmental friendliness, safety and stability. In order to meet the development demand of flexible and miniaturized electronic products, the development of flexible electrode materials for high energy density flexible lithium-ion batteries has become an important research direction.

[0003] Carbon materials are currently the most commonly used negative electrode materials for lithium-ion batteries, mainly due to their volume expansion of only about 10%, suitable cycle life, and low delithiation voltage platform [1-2]. Among the many carbon materials, carbon nanofibers exhibit high mechanical flexibility, short radial effective lithium ion diffusion channels, open fiber gaps that can relieve strain, etc., which can realize the design of macroscopic flexible electrode structures that meet the needs of weaving and large-scale deformation. As a flexible electrode material, it is widely used in wearable electronic devices [3-4].

[0004] Currently, carbon nanofibers are produced on a large scale by carbonizing electrospun polymer / pitch nanofiber precursors at temperatures above 3000°C [5-6]. The strength, conductivity and electrochemical activity of these carbon nanofibers require a certain degree of graphite orientation, which is achieved by creating and maintaining the orientation of polymer chains throughout the stabilization, melting and carbonization synthesis process. However, the main disadvantages of this traditional method are the need for additional preparation of polymer nanofibers, time-consuming synthesis and high energy consumption. In addition, the carbon nanofibers formed with graphite rings, graphite circles and onion-like graphite structures present closed graphene layers and small open intercrystalline gaps, which are very unfavorable for the insertion, diffusion and storage of lithium ions. In addition, the preparation method of preparing carbon nanofibers by pyrolysis of specific carbon sources under transition metal catalysis at temperatures below 1000°C usually exhibits a mixed layer structure with a low degree of graphitization and excessive interlayer distance. Although amorphous carbon nanofibers can store lithium ions through pores, defects, functional groups and disordered interlayers, a large portion of these lithium storage sites are irreversible, which leads to low initial cycle efficiency and long-term cycle capacity decay [7]. The crystallinity (sp3 / sp2 carbon ratio), orientation and interlayer spacing of carbon materials are three important parameters that affect their mechanical strength, electronic conductivity and lithium ion insertion / extraction behavior [1]. In contrast, natural graphite with perfectly ordered graphene layers and an appropriate d(002) spacing of 0.335nm has been shown to be a highly reversible negative electrode material [8]. The above structure-activity relationship analysis shows that it is urgent to develop new high-performance carbon nanofiber negative electrode materials for flexible lithium-ion batteries to meet the application requirements of today's flexible lithium-ion batteries for high specific capacity and high power.

[0005] Therefore, exploring a class of effective carbon precursor materials as solid carbon sources, and establishing an effective low-temperature synthesis strategy to directly prepare carbon nanofibers with good graphitization, controllable orientation and interlayer spacing, obtain highly active carbon skeleton structure, high electronic conductivity, and high ion transport properties, and further obtain good discharge specific capacity, charge and discharge cycle stability, and rate performance, is an urgent need to realize the large-scale application of high-performance carbon nanofiber flexible negative electrode materials.

[0006] References

[0007] [1]Wang,G.;Yu,M.;Feng,X.,Carbon materials for ion-intercalationinvolved rechargeable battery technologies.Chem.Soc.Rev.2021,50(4),2388-2443.

[0008] [2]Lauro,S.N.;Burrow,J.N.;Mullins,C.B.,Restructuring the lithium-ionbattery:A perspective on electrode architectures.eScience 2023,3(4),100152.

[0009] [3]Chen,S.;Qiu,L.;Cheng,H.M.,Carbon-based fibers for advancedelectrochemical energy storage devices.Chem.Rev.2020,120(5),2811-2878.

[0010] [4]Huang,T.;Yang,X.;Xiao,J.;Gao,H.;Wang,Y.;Liu,H.;Wang,G.,Advancinglow-dimensional flexible energy devices for wearabletechnology.J.Mater.Chem.A 2024,12,13672-13681.

[0011] [5]Chen,L.;Mei,S.;Fu,K.;Zhou,J.,Spinning the future:The convergenceof nanofiber technologies and yarn fabrication.ACS nano 2024,18(24),15358-15386.

[0012] [6]Kurban,Z.;Lovell,A.;Jenkins,D.;Bennington,S.;Loader,I.;Schober,A.;Skipper,N.,Turbostratic graphite nanofibres from electrospun solutions of PANin dimethylsulphoxide.Eur.Polym.J.2010,46(6),1194-1202.

[0013] [7] Lee, J.; An, K.; Ju, J.; Cho, B.; Cho, W.; Park, D.; Yun, K., Electrochemical properties of PAN-based carbon fibers as anodes for rechargeable lithium ionbatteries. Carbon 2001, 39, 1299-1305.

[0014] [8]Wang, R.; Wang, L.; Liu, R.; Li, Summary of the invention

[0015] In order to explore a class of effective carbon precursor materials as solid carbon sources, an effective low-temperature synthesis strategy is established to directly prepare carbon nanofibers with good graphitization, controllable orientation and interlayer spacing, obtain highly active carbon skeleton structure, high electronic conductivity, and high ion transport properties, and further improve the discharge specific capacity, charge and discharge cycle stability, and rate performance of flexible lithium-ion batteries. The present invention provides a lithium-ion battery nitrogen-doped carbon nanofiber negative electrode material and a preparation method thereof.

[0016] The object of the present invention is achieved in that:

[0017] A nitrogen-doped carbon nanofiber negative electrode material for a lithium-ion battery is characterized in that the material has a tubular core-shell structure, the outer shell is a bamboo-shaped hollow nitrogen-doped carbon nanotube graphite fiber shell layer, and the inner core is a solid graphite fiber core layer.

[0018] In the above-mentioned nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries, the outer shell is a longitudinally grown bamboo-shaped hollow nitrogen-doped carbon nanotube graphite fiber shell layer, and the inner core is a transversely V-shaped grown solid structure graphite fiber core layer.

[0019] In the above-mentioned nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries, the length of the bamboo-shaped hollow nitrogen-doped carbon nanotube graphite fiber shell is between 0.1 and 100 μm, the tube diameter is between 10 and 500 nm, and the carbon wall thickness is 2 to 50 nm.

[0020] In the above-mentioned nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries, the length of the graphite fiber core layer of the solid structure is between 0.1 and 100 μm, and the diameter is between 8 and 498 nm.

[0021] In the above-mentioned nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries, the volume of the solid structure graphite fiber core layer of the lateral growth structure accounts for between 10% and 95%.

[0022] In the above-mentioned nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries, the hollow nitrogen-doped carbon nanotube graphite fiber shell with a high degree of graphitization, the directional growth of the solid structure graphite fiber core layer, and the increased graphite fiber interlayer spacing show a highly active carbon skeleton structure, high electronic conductivity, and high lithium ion transport properties, which further improve the lithium storage capacity, rate performance and cycle stability in the application of negative electrode materials.

[0023] The method for preparing the nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries comprises the following steps:

[0024] 1) Using nitrogen heterocycles and polycyclic aromatic hydrocarbons as carbon sources and nitrogen sources, and mixing them with transition metal salts to form a slurry and drying them to obtain a mixed powder material;

[0025] 2) calcining the mixed powder material of step 1) under a high temperature inert atmosphere and cooling the mixture to obtain a nitrogen-doped carbon nanofiber negative electrode material embedded with transition metal particles;

[0026] 3) The nitrogen-doped carbon nanofiber negative electrode material embedded with transition metal particles obtained in step 2) is subjected to hydrothermal treatment in an acid solution to remove the transition metal particles, and then dried to obtain the nitrogen-doped carbon nanofiber negative electrode material.

[0027] In the above preparation method, the nitrogen heterocycle in step 1) is one or more combinations of melamine, hexamethylenetetramine, hexamethylmelamine, melamine formaldehyde resin, triazole, adenine, biimidazole, pteridine, triazacyclododecane, and tetraazacyclopentadecane; the polycyclic aromatic hydrocarbons are one or more combinations of naphthalene, acenaphthene, anthracene, phenanthrene, fluorene, pyrene, fluoranthene, perylene, and anthranthene; and the transition metal salt is one or more combinations of carbonates, nitrates, and chlorides of transition metals iron, cobalt, and nickel.

[0028] In the above preparation method, step 2) includes the following steps: sintering the mixed powder material at 200-500°C in a nitrogen atmosphere for 0.5-5 hours, and sintering at 600-1100°C for 0.5-72 hours, and cooling to room temperature to obtain a nitrogen-doped carbon nanofiber negative electrode material embedded with transition metal particles.

[0029] In the above preparation method, step 3) includes the following steps: the nitrogen-doped carbon nanofiber negative electrode material embedded with transition metal particles is hydrothermally treated at 80-200°C in a 2-6M HCl solution for 1-60 hours to remove the metal particles, and is washed with deionized water and dried to obtain the nitrogen-doped carbon nanofiber negative electrode material.

[0030] Positive and beneficial effects: The nitrogen-doped carbon nanofiber negative electrode material prepared by the present invention has a novel structure and a tubular core-shell structure, wherein the outer shell layer is a longitudinally grown bamboo-shaped hollow nitrogen-doped carbon nanotube graphite fiber shell layer, and the inner core layer is a transversely V-shaped solid structure graphite fiber core layer. The graphene fiber layer arranged and grown in the longitudinal and transverse directions and the increased interlayer spacing of the graphite fiber make the nitrogen-doped carbon nanofiber negative electrode material show a highly active carbon skeleton structure, high electronic conductivity, and high lithium ion transmission characteristics, and further obtain better lithium storage capacity, rate performance and cycle stability in the application of negative electrode materials; the present invention uses nitrogen heterocycles and polycyclic aromatic hydrocarbons as a specific type of two-component carbon source, and through the carbon nanotube space-constrained metal top catalytic structure reconstruction strategy, it can directly prepare nitrogen-doped carbon nanofiber negative electrode materials with controllable structure and morphology, and presents a higher application performance advantage. In addition, the entire process does not require the additional preparation of polymer nanofiber precursors with a specific orientation. The synthesis time is short and it can be prepared at a relatively low reaction temperature of 800-1100°C. It has low energy consumption, low preparation cost, simple process, and is easy to realize the industrial production of nitrogen-doped carbon nanofiber negative electrode materials, which can meet the large-scale application requirements of flexible lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic diagram of the synthesis of the nitrogen-doped carbon nanofiber material prepared in Example 1 of the present invention;

[0032] Figure 2 The scanning electron microscope and transmission electron microscope images of the nitrogen-doped carbon nanofiber material prepared in Example 1 of the present invention;

[0033] Figure 3 This is the first charge and discharge performance diagram of the nitrogen-doped carbon nanofiber material prepared in Example 1 of the present invention;

[0034] Figure 4 The 600 charge-discharge cycle stability of the nitrogen-doped carbon nanofiber material prepared in Example 1 of the present invention;

[0035] Figure 5 This is the rate performance of the nitrogen-doped carbon nanofiber material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] The present invention will be further described below in conjunction with specific embodiments:

[0037] Example 1

[0038] (1) Using nitrogen heterocycles and polycyclic aromatic hydrocarbons as carbon and nitrogen sources, 1.5 g of melamine (carbon and nitrogen source precursors of nitrogen heterocycles) and 1.5 g of naphthalene (carbon source of polycyclic aromatic hydrocarbons) were dissolved in 15 ml of acetic acid solution and stirred for 30 minutes. Then, 1.5 g of CoCl2·6H2O was mixed to form a slurry, which was dried at 80°C for 24 hours and ground to obtain a mixed powder material.

[0039] (2) The mixed powder material was sintered at 350°C for 1 hour and at 950°C for 3 hours in a nitrogen atmosphere, and then cooled to room temperature to obtain a nitrogen-doped carbon nanofiber negative electrode material embedded with transition metal cobalt (CNT-CNP@Co).

[0040] (3) The nitrogen-doped carbon nanofiber negative electrode material embedded with transition metal cobalt was hydrothermally treated at 150°C in a 4M HCl solution for 48 hours to remove the transition metal cobalt, and then washed with deionized water and dried to obtain a carbon nanotube-carbon nanoprism nanofiber material (CNT-CNP).

[0041] CNT-CNP material: polyvinylidene fluoride were mixed in a mass ratio of 9:1, and nitrogen methyl pyrrolidone was used as a solvent to prepare a slurry and coat it on the surface of copper foil (diameter 13 mm, thickness 0.3 mm). The coating density was 1.0 mg / cm2, and it was dried at 120°C for 24 hours to make a working electrode sheet. Lithium foil was used as the counter electrode and reference electrode, the electrolyte was 1.0MLiPF6 / EC (ethylene carbonate): DMC (dimethyl carbonate) = 1:1 (V / V), and Celgard 2300 membrane (25μm thick polyethylene) was used as a diaphragm. Button cells (CR2032) were assembled in a high-purity argon glove box. Constant current charge and discharge tests were performed using a Land battery tester to study the charge and discharge specific capacity and cycle performance of CNT-CNP materials. Voltage test range: 0.01-3.0V (vs Li / Li + ).

[0042] like Figure 1 As shown, the present invention discloses a class of solid nitrogen heterocycles (such as melamine, hexamethylmelamine, triazole, adenine, etc.) and polycyclic aromatic hydrocarbons (such as naphthalene, acenaphthene, anthracene, phenanthrene, fluorene, pyrene, fluoranthene, perylene, anthranthene, etc.) as a two-component organic carbon source, through pyrolysis, carbothermal reduction and CNT spatial confinement metal catalyzed carbon rearrangement reaction, successfully synthesizing transition metal-containing nitrogen-doped carbon nanofiber materials ( Figure 1). The obtained material is further hydrothermally treated in hydrochloric acid to remove the metal components contained therein, and the target product nitrogen-doped carbon nanofiber material can be obtained, which is used as a flexible electrode material in flexible battery devices.

[0043] Figure 2 This is a scanning electron microscope image of CNT-CNP@Co nanofibers, in which the bamboo-like hollow nitrogen-doped carbon nanotube graphite fiber shell layer CNT is completely coated on the solid structure of the graphite fiber core layer CNP, forming an almost solid carbon nanofiber with an arc-shaped concave surface. The diameter of the CNT shell layer is about 300-350nm, the carbon wall thickness is about 10nm, and the length is 2-5μm. The diameter of the CNP core layer is about 290-340nm, and the length is the same as CNT, which is 2-5μm ( Figure 2 ad). Among them, the solid structure graphite fiber core layer CNP grown in a transverse V-shape and the bamboo-shaped hollow nitrogen-doped carbon nanotube graphite fiber shell layer CNT ( Figure 2 eh) are cross-linked with each other. Figure 2 fh and Figure 2 ik, the light-colored herringbone regions are regularly distributed along the axial direction in the dark CNPs, indicating the presence of pores and disconnected lateral graphene layers. The CNPs composed of 9.4-11.3nm thick lateral graphene sheets and a certain number of 11.4-11.9nm wide voids not only increase the Li + The amount of open graphene interstitial space stored accelerates the Li + The diffusion of carbon nanofibers also improves the overall electronic conductivity and mechanical strength of carbon nanofibers ( Figure 2 This novel structure can ensure that the nitrogen-doped carbon nanofiber negative electrode material has good electronic conductivity, ion diffusivity, structural stability and mechanical strength, so that it can show excellent charge and discharge performance, rate performance and cycle stability in flexible lithium-ion battery applications.

[0044] from Figure 3 It can be seen that the charge and discharge test was carried out at 0.05A / g (0.1C), and the first discharge and charge specific capacities of the nitrogen-doped carbon nanofiber material CNT-CNP were 576mAh g -1 and 482mAh g -1 , and the coulombic efficiency is 84%. Compared with the comparative example 1 CNT, the nitrogen-doped carbon nanofiber material CNT-CNP of the present invention has a larger initial reversible capacity, and compared with the comparative example 2 SCNF material, it has a larger initial reversible capacity and a higher coulombic efficiency. The excellent charge and discharge performance of CNT-CNP is mainly attributed to the fact that the SEI film formed on the electrode surface of this structure is less, the number of ordered graphene layers is larger, and more reversible Li can be stored without consuming electrolyte. + .

[0045] from Figure 4 It can be seen that after 600 charge and discharge cycles at 0.5A / g (1C), the discharge capacity of nitrogen-doped carbon nanofiber material CNT-CNP is still as high as 378mAhg -1 The capacity retention rate is 94.5%, showing high charge and discharge cycle stability.

[0046] from Figure 5 It can be seen that at 0.05 (0.1C), 0.25 (0.5C), 0.5 (1C), 1 (2C) and 2.5 (5C) Ag -1 After 30 cycles of charge and discharge, the discharge specific capacities of the nitrogen-doped carbon nanofiber material CNT-CNP were 475, 445, 400, 353 and 303 mAh g, respectively. -1 , showing excellent charge and discharge rate performance.

[0047] Example 2

[0048] Step (1-3) is basically the same as the preparation process of Example 1, 3 grams of melamine (carbon source and nitrogen source precursor of nitrogen heterocyclics) and 0.9 grams of benzopyrene (carbon source of polycyclic aromatic hydrocarbons) are dissolved in 15 ml of acetic acid solution and stirred for 30 minutes. Then, 1.5 grams of NiCl2·6H2O are mixed to form a slurry, dried at 80°C for 24 hours, and ground to obtain a mixed powder material.

[0049] (2) The mixed powder material was sintered at 350°C for 1 hour and at 950°C for 3 hours in a nitrogen atmosphere, and then cooled to room temperature to obtain a nitrogen-doped carbon nanofiber negative electrode material embedded with transition metal nickel (CNT-CNC@Ni).

[0050] (3) The nitrogen-doped carbon nanofiber negative electrode material embedded with transition metal nickel was hydrothermally treated at 150°C for 48 hours in a 4M HCl solution to remove the transition metal nickel, and then washed with deionized water and dried to obtain a carbon nanotube-carbon nanocylinder nanofiber material (CNT-CNC). The electrochemical properties of the CNT-CNC nanofiber material are shown in Table 1.

[0051] Comparative Example 1

[0052] Steps (1-3) are basically the same as the preparation process of Example 1, 3 grams of melamine (carbon source and nitrogen source precursor of nitrogen heterocyclic rings) are dissolved in 15 ml of acetic acid solution and stirred for 30 minutes. Then, 1.5 grams of NiCl2·6H2O are mixed to form a slurry, which is dried at 80°C for 24 hours and ground to obtain a mixed powder material.

[0053] (2) The mixed powder material was sintered at 350°C for 1 hour and at 950°C for 3 hours in a nitrogen atmosphere, and then cooled to room temperature to obtain a nitrogen-doped carbon nanofiber negative electrode material (CNT@Ni) embedded with transition metal nickel.

[0054] (3) The nitrogen-doped carbon nanofiber negative electrode material embedded with transition metal nickel was hydrothermally treated at 150°C for 48 hours in a 4M HCl solution to remove the transition metal nickel, and then washed with deionized water and dried to obtain a hollow carbon nanotube material (CNT) without a solid structural graphite fiber core layer. The electrochemical properties of the CNT nanofiber material are shown in Table 1.

[0055] Comparative Example 2

[0056] 2 g of polyacrylonitrile and 1 g of CoCl2·6H2O were dissolved in 15 g of dimethylformamide and stirred for 30 min to obtain a transparent solution. The flow rate of the electrospinning solution was controlled at 2 mL h using a syringe pump. -1 The electrospinning process was conducted at 100 kV m -1 The obtained organic nanofibers were annealed in air at 300°C to partially oxidize the nanofibers. They were then further heated at 950°C for 3 hours in nitrogen and then cooled to room temperature to obtain carbon nanofibers (SCNF@Co) embedded with transition metal cobalt prepared by electrospinning. The carbon nanofiber material embedded with transition metal cobalt was hydrothermally treated at 150°C in a 4M HCl solution for 48 hours to remove the transition metal cobalt, and then washed with deionized water and dried to obtain a carbon nanofiber material (SCNF). The electrochemical properties of the SCNF nanofiber material are shown in Table 1.

[0057] Table 1. Charge and discharge performance of carbon nanofiber materials in examples and comparative examples

[0058]

[0059] As can be seen from Table 1, compared with CNT and SCNF materials, the nitrogen-doped carbon nanofiber material in the present invention has a higher discharge specific capacity and excellent cycle stability. After 600 cycles, the capacity retention rate is above 94.5%, which can meet the application requirements of high-performance and high-stability lithium-ion batteries.

[0060] The preparation method of the present invention discloses a class of solid nitrogen heterocycles (such as melamine, hexamethylmelamine, triazole, adenine, etc.) and polycyclic aromatic hydrocarbons (such as naphthalene, anthracene, pyrene, perylene, etc.) as a two-component organic carbon source, and can directly prepare a transition metal-containing nitrogen-doped carbon nanofiber material with an adjustable tubular core-shell structure and controllable graphene fiber layer orientation at a relatively low temperature of 800-1100° C. by pyrolysis, carbon thermal reduction and CNT space-restricted metal-catalyzed carbon rearrangement reaction. The obtained material is further hydrothermally treated in hydrochloric acid to remove the contained metal components, so that the target product nitrogen-doped carbon nanofiber material can be obtained, which is used as a flexible electrode material in a flexible lithium-ion battery device. The present invention uses a class of solid nitrogen heterocycles and polycyclic aromatic hydrocarbons as cheap carbon sources and nitrogen source precursors. In the preparation of nitrogen-doped carbon nanofiber materials, the entire process does not require the additional preparation of carbon fiber polymer precursors with a specific orientation. The preparation cost is low, the process is simple, and thermal decomposition synthesis can be achieved at a relatively low temperature. It has great economic and social benefits, is easy to realize the industrial production of carbon nanofibers, and can meet the large-scale application requirements of flexible lithium-ion batteries.

[0061] The nitrogen-doped carbon nanofiber material prepared by the present invention can be characterized by the following method: nitrogen-doped carbon nanofiber material: polyvinylidene fluoride are mixed in a mass ratio of 9:1, and nitrogen methyl pyrrolidone is used as a solvent to prepare a slurry and apply it to the surface of copper foil (diameter 13 mm, thickness 0.3 mm), the coating density is 1.0 mg / cm2, and it is dried at 120°C for 24h to prepare a working electrode sheet. Lithium foil is used as a counter electrode and a reference electrode, the electrolyte is 1.0M LiPF6 / EC (ethylene carbonate): DMC (dimethyl carbonate) = 1:1 (V / V), and Celgard 2300 film (25μm thick polyethylene) is used as a diaphragm. A button cell (CR2032) is assembled in a high-purity argon glove box. A constant current charge and discharge test is performed using a Land battery tester to study the charge and discharge specific capacity, cycle performance, and rate performance of the nitrogen-doped carbon nanofiber material. The nitrogen-doped carbon nanofiber material prepared above exhibits good charge-discharge cycle performance and rate performance when applied to flexible lithium-ion batteries.

[0062] The nitrogen-doped carbon nanofiber prepared by the present invention has a novel structure and a tubular core-shell structure, wherein the outer shell layer is a longitudinally grown bamboo-shaped hollow nitrogen-doped carbon nanotube graphite fiber shell layer, and the inner core layer is a transversely V-shaped solid structure graphite fiber core layer. The graphene fiber layer arranged and grown in the longitudinal and transverse directions and the increased interlayer spacing of the graphite fiber make the nitrogen-doped carbon nanofiber negative electrode material exhibit a highly active carbon skeleton structure, high electronic conductivity, and high lithium ion transmission characteristics, and further obtain better lithium storage capacity, rate performance, and cycle stability in the application of negative electrode materials.

[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A nitrogen-doped carbon nanofiber negative electrode material for a lithium-ion battery, characterized in that: The material has a tubular core-shell structure, wherein the outer shell is a bamboo-shaped hollow nitrogen-doped carbon nanotube graphite fiber shell layer, and the inner core is a solid graphite fiber core layer.

2. The nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries according to claim 1, characterized in that: In the above-mentioned nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries, the outer shell is a longitudinally grown bamboo-shaped hollow nitrogen-doped carbon nanotube graphite fiber shell layer, and the inner core is a transversely V-shaped grown solid structure graphite fiber core layer.

3. The nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries according to claim 1, characterized in that: In the above-mentioned nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries, the length of the bamboo-shaped hollow nitrogen-doped carbon nanotube graphite fiber shell is between 0.1 and 100 μm, the tube diameter is between 10 and 500 nm, and the carbon wall thickness is 2 to 50 nm.

4. The nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries according to claim 1, characterized in that: In the above-mentioned nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries, the length of the graphite fiber core layer of the solid structure is between 0.1 and 100 μm, and the diameter is between 8 and 498 nm.

5. The nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries according to claim 1, characterized in that: In the above-mentioned nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries, the volume of the solid structure graphite fiber core layer of the lateral growth structure accounts for between 10% and 95%.

6. The nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries according to claim 1, characterized in that: In the above-mentioned nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries, the hollow nitrogen-doped carbon nanotube graphite fiber shell with a high degree of graphitization, the directional growth of the solid structure graphite fiber core layer, and the increased graphite fiber interlayer spacing show a highly active carbon skeleton structure, high electronic conductivity, and high lithium ion transport properties, which further improve the lithium storage capacity, rate performance and cycle stability in the application of negative electrode materials.

7. The method for preparing the nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries according to any one of claims 1 to 6, comprising the following steps: 1) Using nitrogen heterocycles and polycyclic aromatic hydrocarbons as carbon sources and nitrogen sources, and mixing them with transition metal salts to form a slurry and drying them to obtain a mixed powder material; 2) calcining the mixed powder material of step 1) under a high temperature inert atmosphere and cooling the mixture to obtain a nitrogen-doped carbon nanofiber negative electrode material embedded with transition metal ions; 3) The nitrogen-doped carbon nanofiber negative electrode material embedded with transition metal ions obtained in step 2) is subjected to hydrothermal treatment in an acid solution to remove the transition metal ions, and then dried to obtain the nitrogen-doped carbon nanofiber negative electrode material.

8. The method for preparing the nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries according to claim 7, characterized in that: In the above preparation method, the nitrogen heterocycle in step 1) is one or more combinations of melamine, hexamethylenetetramine, hexamethylmelamine, melamine formaldehyde resin, triazole, adenine, biimidazole, pteridine, triazacyclododecane, and tetraazacyclopentadecane; the polycyclic aromatic hydrocarbons are one or more combinations of naphthalene, acenaphthene, anthracene, phenanthrene, fluorene, pyrene, fluoranthene, perylene, and anthranthene; and the transition metal salt is one or more combinations of carbonates, nitrates, and chlorides of transition metals iron, cobalt, and nickel.

9. The method for preparing the nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries according to claim 7, characterized in that: In the above preparation method, step 2) includes the following steps: sintering the mixed powder material at 200-500°C in a nitrogen atmosphere for 0.5-5 hours, and sintering at 600-1100°C for 0.5-72 hours, and cooling to room temperature to obtain a nitrogen-doped carbon nanofiber negative electrode material embedded with transition metal ions.

10. The method for preparing the nitrogen-doped carbon nanofiber negative electrode material for lithium-ion batteries according to claim 7, characterized in that: In the above preparation method, step 3) includes the following steps: the nitrogen-doped carbon nanofiber negative electrode material embedded with transition metal ions is hydrothermally treated at 80-200°C in a 2-6M HCl solution for 1-60 hours to remove the metal ions, and is washed with deionized water and dried to obtain the nitrogen-doped carbon nanofiber negative electrode material.